Expressions of Criticsm towards Social Problems in Poetry from Ancient Age, Modern Age, and Contemporary Age - Yenny Marlim; Therecia Oscar (Journal of Language, Literature and Teaching, 2022)
The purpose of this research is to reveal the forms of ancient, modern and contemporary poetry in expressing social problems and the reasons for the expressions of social criticism. The design of this research is a descriptive qualitative. The objects of the research are the forms of expression towards social criticism and the reasons behind them which are found in the ancient Tang poetry “Zi Jing Fu Feng Xian Xian Yong Huai Wu Bai Zi自京赴奉先县咏怀五百字”, the modern poetry “Da Yan He Wo - De Bao大堰河——我的保姆”, and the contemporary poetry “Xiang Chou乡愁”. The results of the research show that there are 26 forms of expression of social criticism in the three poems, including 13 straightforward social criticism (50%), 6 symbolic social criticism (23.08%), 2 cynical social criticism (7.69%) and 5 explanatory social criticism (19.23%). There are three reasons for the expressions of social criticism: (1) the historical aspect (national administration), (2) psychological aspect (sharpening the author's expression attitude), and (3) imagery.Key Words: Social Criticism, Expressions Form, Poem